2021
DOI: 10.1177/21582440211029910
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life of Older Adults in a Multiethnic Metropolitan: An Analysis of CASP-19

Abstract: This study examines the well-being of older Malaysians, using Control, Autonomy, Self-Realization, and Pleasure (CASP-19) score. Data for this study came from a cross-sectional survey on older adults living in a multiethnic metropolitan in Malaysia. The sample comprised Asia’s three major ethnic groups. Bivariate and multivariate analyses show significant ethnic differentials in quality of life (QoL). Results from multiple regression show that CASP-19 is strongly influenced by self-rated health and the ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…For instance, Loh et al [50] reported that Malay adolescents recorded lower HRQOL, as compared to adolescents of other ethnicities [34]. In a more recent study, Lai et al found that the Malay elderly group recorded higher mean control, autonomy, self-realisation, and pleasure (CASP-19) score (than the Chinese and Indian elderly groups), suggesting higher QOL instead [51]. Therefore, it is imperative to further explore these health inequalities across ethnicities in Malaysia for optimal health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Loh et al [50] reported that Malay adolescents recorded lower HRQOL, as compared to adolescents of other ethnicities [34]. In a more recent study, Lai et al found that the Malay elderly group recorded higher mean control, autonomy, self-realisation, and pleasure (CASP-19) score (than the Chinese and Indian elderly groups), suggesting higher QOL instead [51]. Therefore, it is imperative to further explore these health inequalities across ethnicities in Malaysia for optimal health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…(5,6) In addition, old age brings with it increasing vulnerability as a result of physical and functional deterioration, and the attendant burdens on health and social care services. (7,8) Maintaining good health and well-being is often presented as an indicator of healthy or successful aging. (9,10) Therefore, older adults are an important issue in which a priority challenge is represented for health authorities and health professionals, whose function is to provide a better quality of life for successful aging.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural and religious norms in Malaysia create intense family relations and support systems, which serve as a crucial source of elderly care (Ahmad Ramli et al, 2022 ). Malaysia is widely known as a multicultural country, with the main ethnic groups consisting of the Malays, Chinese, and Indians (Lai & Tey, 2021 ). The multi-ethnic populations can provide insights into understanding demographic variables associated with social support for older caregivers in Malaysia.…”
Section: Introductionmentioning
confidence: 99%